2022
DOI: 10.1097/md.0000000000029235
|View full text |Cite
|
Sign up to set email alerts
|

Risk of developing cognitive impairment on patients with chronic obstructive pulmonary disease

Abstract: Background: The increasing number of chronic obstructive pulmonary disease (COPD) incidence has led to a great negative impact on older people's lives. This chronic disease was a critical and independent risk factor for cognitive function impairment in the elderly with mild cognitive impairment as a frequent feature. This systematic review aimed to examine the risk of developing cognitive impairment in COPD. Methods: A structured search of the literature was conducted u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…38 A major component of post-warning prevention and management strategies includes multiple factors in addition to age, such as many treatable NCDs, including diabetes, hypertension, and cardiovascular disease, as well as lifestyle habits. [39][40][41] Chronic diseases are considered as one of the major causes of age-related cognitive decline. For high-risk populations, such as patients with T2DM, diabetes control led to significant improvement in the cognitive status of patients.…”
Section: Discussionmentioning
confidence: 99%
“…38 A major component of post-warning prevention and management strategies includes multiple factors in addition to age, such as many treatable NCDs, including diabetes, hypertension, and cardiovascular disease, as well as lifestyle habits. [39][40][41] Chronic diseases are considered as one of the major causes of age-related cognitive decline. For high-risk populations, such as patients with T2DM, diabetes control led to significant improvement in the cognitive status of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Current prevalence estimates of cognitive impairment in COPD patients range from 4% to 61% [16,17]. The wider variations in these estimates are attributed to the study populations, assessment and diagnostic tools, and methodological designs [18,19]. A recent meta-analysis of 14 studies reported that, on average, 32% of patients with COPD are affected by cognitive impairment and that 1 in 4 people with COPD suffer from mild cognitive impairment [18].…”
Section: Loss Of Memorymentioning
confidence: 99%
“…Notably, cognitive impairment is widespread in patients with COPD ( Charbek et al, 2019 ). The prevalence of cognitive impairment is reported to be about 16%–85% in patients with COPD ( Simargi et al, 2022 ; Yohannes et al, 2017 ). Furthermore, COPD increases the risk of cognitive impairment by about 2.5 times ( Dodd, Getov & Jones, 2010 ).…”
Section: Introductionmentioning
confidence: 99%